Dementia-Friendly Communities: Exploring Terms used to Describe Dementia, Attitudes and Reactions Towards People with Dementia in Ilembe District, South Africa. (July 2023) - Mfene, Xoli P; Pillay, Basil J
Background: People with dementia often experience stigma, abuse and social exclusion in their communities. Thus, developing dementia-friendly communities is a priority in the fight against dementia. Objectives: This study investigated communities' attitudes towards people with dementia by exploring the colloquial terms referring to dementia and the social tolerance toward people with dementia. Methods: A cross-sectional household study, using individual interviews, was conducted in the iLembe district, South Africa, with 300 participants aged ≥18 years. Data was collected between 2018 and 2019. Data was analysed using descriptive and reflexive thematic analyses. Results: Two themes related to local dementia terms were identified: (i) There are no known local terms synonymous with the term dementia; (ii) Communities use inaccurate and stigmatizing terms to describe dementia. The terms identified did not accurately describe dementia, and others had negative connotations toward people with dementia. Although most participants reported being tolerant, neighbourly, and friendly towards people with dementia, their tolerance decreased when personal interaction was required with a person with dementia. Most participants reported a more agreeable attitude when considering being neighbours rather than family members of people with dementia, and 50.3% reported that their communities discriminate against older people with dementia. Conclusion: The identified dementia terms did not promote dementia-friendly societies. Appropriate dementia terms are crucial for changing social intolerance and negative perceptions of people with dementia and promoting a dementia-friendly culture in South African communities. Terms that encourage and perpetuate stigma against people with dementia must be replaced with terms that promote inclusion and tolerance.